Initial experience of transpapillary gallbladder biopsy using newly designed device delivery system - Yane, Kei; Tomita, Yusuke; Yoshida, Masahiro; Sasaki, Kou; Imagawa, Takayuki; Morita, Kotaro; Ihara, Hideyuki; Minagawa, Takeyoshi; Okagawa, Yutaka; Hirayama, Michiaki; Sumiyoshi, Tetsuya; Kondo, Hitoshi (Endoscopy International Open, 2023)
Transpapillary gallbladder biopsy has been reported for the diagnosis of gallbladder disease, and this procedure requires special biopsy forceps or a large-diameter pusher catheter. We retrospectively examined consecutive patients who underwent transpapillary gallbladder biopsy using a newly designed device delivery system (Endosheather; Piolax Medical Device, Kanagawa, Japan). We evaluated 11 patients (median age, 71 years [28–85]) who underwent transpapillary gallbladder biopsy from June 2021 to July 2022. The selective gallbladder cannulation and delivery system insertion success rate was 90.9% (10/11). The target lesion biopsy success rate was 63.6% (7/11). The biopsy time (i.e., time to completion of biopsy after successful guidewire placement) was 8.7 (5.4–32.7) min. In 1 patient in whom all 6 gallbladder bile juice cytology results were benign, the biopsy result was suspicious of adenocarcinoma. The final diagnosis for this patient was gallbladder cancer. Adverse events occurred in 2 patients. In 1 patient, acute cholecystitis occurred and required emergency surgery. Transpapillary gallbladder biopsy using the Endosheather is a potential option for the diagnosis of gallbladder disease. A good indication for this technique is considered to be wall thickening at the gallbladder fundus, where it is difficult to differentiate between benign and malignant lesions by imaging modalities such as ultrasonography or endoscopic ultrasound. The addition of transpapillary gallbladder biopsy may be advantageous when performing bile juice cytology using a nasogallbladder drainage tube for the diagnosis of gallbladder disease.